1985
DOI: 10.1002/jlac.198519850708
|View full text |Cite
|
Sign up to set email alerts
|

5‐Methylcumarin‐Derivate aus Lycoseris latifolia

Abstract: Aus oberirdischen Teilen von Lycoseris latifolia wurden neun Cumarin-Derivate isoliert, die sehr wahrscheinlich biogenetisch durch Kondensation von 4-Hydroxy-5-methylcumarin mit einem Sesquiterpenaldehyd gebildet werden, wonach sich verschiedene Umwandlungen und Abbaureaktionen anschlieBen. Die Strukturen wurden durch Hochfeld-NMR-Spektroskopie geklart. NOE-Differenzspektroskopie ermoglichte eine eindeutige Zuordnung aller Konfigurationen. Die chemotaxonomische Bedeutung dieser Verbindungen wird kurz diskutier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 18 publications
(1 reference statement)
3
5
0
Order By: Relevance
“…6). Spectroscopic and spectrometric data confirmed all structures (Bohlmann et al, 1985;Caputo et al, 1976). However, we could obtain and report in this work some more accurate H-H coupling constants for compound 1, (see experimental part and Supplementary material for NMR spectra) which structure and relative stereochemistry was previously unequivocally elucidated by us using X-ray single-crystal diffraction analysis (Brito et al, 2014).…”
Section: Isolation and Structural Elucidation Of Compoundssupporting
confidence: 51%
See 2 more Smart Citations
“…6). Spectroscopic and spectrometric data confirmed all structures (Bohlmann et al, 1985;Caputo et al, 1976). However, we could obtain and report in this work some more accurate H-H coupling constants for compound 1, (see experimental part and Supplementary material for NMR spectra) which structure and relative stereochemistry was previously unequivocally elucidated by us using X-ray single-crystal diffraction analysis (Brito et al, 2014).…”
Section: Isolation and Structural Elucidation Of Compoundssupporting
confidence: 51%
“…13 C NMR (100.13 MHz, CDCl 3 , from C-3 to C-11: ı = 46.8 (t), 206.7 (s), 138.4 (s), 123.2 (d), 134.2 (d), 116.2 (d), 160.8 (s), 123.9 (s), 21.3 (9); From C-I' to C-15': ı = 74.4 (d), 48.0 (d), 37.1 (d), 34.0 (t), 32.6(t), 43.5 (d), 144.6 (s), 123.3 (s), 199.8 (s), 48.6 (t), 23.7 (d), 22.6 (q), 22.5 (q), 17.0 (q), 24.1. All spectroscopic data was similar to that previously published (Bohlmann et al, 1985), however since we were using state of the art equipment, we have found the above stated and more defined and accurate proton-proton coupling constants for this compound. , 17.87 (q, C-15 ).…”
Section: Isolation and Structural Elucidation Of Compoundssupporting
confidence: 51%
See 1 more Smart Citation
“…After comparing the NMR data of 1 with those of the characteristic coumarins found in the tribe Mutisieae, the 2 broad doublets at ô 7.23 and 7.35 ppm, a triplet at 7.80 ppm together with the broad CH3 singlet at b =2.80 ppm revealed the presence of a 5-methyl-4-O-substituted coumarin C10-unit. These data are in close agreement with some of the 5methylcoumarins which have been isolated from different genera of this tribe (4)(5)(6)(8)(9)(10)(11). The location of the methyl group at C-S was further supported by the long-range coupling between the methyl and the H-6, 7,8 protons.…”
Section: Resultssupporting
confidence: 88%
“…The isolation of 5-methylcoumaranones A−D ( 1 − 4 ) together with structurally related 5-methylcoumarins and 5-methylphenones 7 containing mono- and sesquiterpene residues enabled us to suggest a biosynthetic relationship between these three groups of compounds in the shrub M. friesiana (Figure ). 4-Hydroxy-5-methylcoumarin (HMC), biosynthesized from acetyl-CoA and malonyl-CoA, has been postulated as the precursor of 5-methylcoumarins. ,, In the first stage, the reaction of HMC with activated mono- and sesquiterpenes present in the essential oil of the plant 4 would be responsible for the formation of mutisichromone and mutisicoumarins A−C . In a second stage, hydrolysis of 5-methylcoumarins with elimination of CO 2 and further keto−enol tautomerization would produce mutisiphenones A−E .…”
Section: Resultsmentioning
confidence: 99%